Control of Reactive Oxygen Species for the Prevention of Parkinson's Disease: The Possible Application of Flavonoids - Tae Yeon Kim; Eunju Leem; Jae Man Lee; Sang Ryong Kim (MDPI AG, 2020)
Oxidative stress reflects an imbalance between the production of reactive oxygen species (ROS) and antioxidant defense systems, and it can be associated with the pathogenesis and progression of neurodegenerative diseases such as multiple sclerosis, stroke, and Parkinson's disease (PD). The application of antioxidants, which can defend against oxidative stress, is able to detoxify the reactive intermediates and prevent neurodegeneration resulting from excessive ROS production. There are many reports showing that numerous flavonoids, a large group of natural phenolic compounds, can act as antioxidants and the application of flavonoids has beneficial effects in the adult brain. For instance, it is well known that the long-term consumption of the green tea-derived flavonoids catechin and epigallocatechin gallate (EGCG) can attenuate the onset of PD. Also, flavonoids such as ampelopsin and pinocembrin can inhibit mitochondrial dysfunction and neuronal death through the regulation of gene expression of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. Additionally, it is well established that many flavonoids exhibit anti-apoptosis and anti-inflammatory effects through cellular signaling pathways, such as those involving (ERK), glycogen synthase kinase-3β (GSK-3β), and (Akt), resulting in neuroprotection. In this review article, we have described the oxidative stress involved in PD and explained the therapeutic potential of flavonoids to protect the nigrostriatal DA system, which may be useful to prevent PD.